Optimization of the Q-P Process Parameters for Low Alloyed Steels with 0.2% C - Jirková H.; Kučerová L.; Aišman D.; Mašek B. (Archives of Metallurgy and Materials, 2014)
In steels which are treated by the quenching and partitioning (Q&P) process, carbon content is one of the crucial parameters because carbon contributes greatly to stabilization of retained austenite and strengthens the material. In the present study, the Q&P process was gradually optimised for two low-alloyed steels with 0.2 % carbon content and with and without Cr addition. The results show that the cooling rate, as well as the austenitizing temperature, has a pronounced effect on microstructure evolution. The strength and elongation in the Mn, Si and Cr-alloyed steel was approx. 900 MPa and more than 30 %, respectively.